2017
DOI: 10.7556/jaoa.2017.110
|View full text |Cite
|
Sign up to set email alerts
|

Single Osteopathic Manipulative Therapy Session Dampens Acute Autonomic and Neuroendocrine Responses to Mental Stress in Healthy Male Participants

Abstract: The application of a single OMTh session to healthy participants induced a faster recovery of heart rate and sympathovagal balance after an acute mental stressor by substantially dampening parasympathetic withdrawal and sympathetic prevalence. The OMTh session also prevented the typical increase in cortisol levels observed immediately after a brief mental challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 28 publications
0
37
1
2
Order By: Relevance
“…The impact of OMT on HRV has previously been investigated and has shown that OMT and other manual therapies typically lead to an increase in parasympathetic dominance ( Delaney et al, 2002 ; Henley et al, 2008 ; Toro-Velasco et al, 2009 ; Buttagat et al, 2011 ; Giles et al, 2013 ). OMT has also been found to effectively counteract the shift of autonomic balance toward a sympathetic prevalence in healthy participants under stressful conditions during a mental challenge task ( Fornari et al, 2017 ), so may have implications for stress reduction and mental health.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of OMT on HRV has previously been investigated and has shown that OMT and other manual therapies typically lead to an increase in parasympathetic dominance ( Delaney et al, 2002 ; Henley et al, 2008 ; Toro-Velasco et al, 2009 ; Buttagat et al, 2011 ; Giles et al, 2013 ). OMT has also been found to effectively counteract the shift of autonomic balance toward a sympathetic prevalence in healthy participants under stressful conditions during a mental challenge task ( Fornari et al, 2017 ), so may have implications for stress reduction and mental health.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely known that stressors tip the ANS balance toward a larger sympathetic prevalence and activate the hypothalamicpituitary-adrenal axis (i.e., increase cortisol levels). In a betweensubject study conducted by our group, a single-session of OMT using craniosacral techniques was performed immediately after an acute mental stressor on a small sample of healthy young men (20-30 years old) (Fornari et al, 2017). We found a smaller reduction in HF-HRV values (obtained from ECG analysis) and a much lower cortisol increment in response to the mental stressor in the OMT group compared with sham treatment (Fornari et al, 2017).…”
Section: Stress Exposurementioning
confidence: 76%
“…In a betweensubject study conducted by our group, a single-session of OMT using craniosacral techniques was performed immediately after an acute mental stressor on a small sample of healthy young men (20-30 years old) (Fornari et al, 2017). We found a smaller reduction in HF-HRV values (obtained from ECG analysis) and a much lower cortisol increment in response to the mental stressor in the OMT group compared with sham treatment (Fornari et al, 2017). While these results must be interpreted with caution given the exploratory nature of this study, in our view the association between OMT and reduced cardiac vagal withdrawal and cortisol rise in response to an acute stress represents an intriguing health-related outcome.…”
Section: Stress Exposurementioning
confidence: 99%
“…McKenzie reinforced the foundational skill of interviewing to determine a patient's symptomatic response to movements and positions [12]. Additional examples of this foundational patient-centric skillset exist within the osteopathic model's method of modulating sympathetic and parasympathetic activity based upon assessment of tone and life stressors [13][14][15]. These essential skills encompass the understanding of the patient's values and beliefs, allow for a shared therapeutic alliance through motivational interviewing, and help to understand one's own implicit bias including when NOT to use hands-on techniques in the patient's plan of care.…”
Section: The Evolution Of Manual Therapy Education: What Are We Waitimentioning
confidence: 99%